ENDOSCOPIC DIAGNOSIS OF HERPES SIMPLEX ESOPHAGITIS: REPORT OF A CASE - YOSHIOKA, Toshifumi; KONO, Hiroshi; OKA, Takefumi; KAWAGUCHI, Kenji; YAMASAKI, Hiroko; MORIMOTO, Shigeto (Japanese Journal of National Medical Services, 1993)
There have been many cases of herpes simplex esophagitis found in autopsies, only but a few cases where this disease was detected in a patient. In ourpresent case, an 81 year old female was admitted with complaints of nausea and anorexia. She was not given any immunosuppressant, nor did she receive nasogastric intubation. An upper gastrointestinal endoscopic examination showed multiple small punchedout ulcers with swollen margins in the middle portion of the esophagus, while an esophageal biopsy specimen revealed ballooning change and intranuclear inclusion (full type). Histochemical study with monoclonal antibody to herpes simplex virus verifyed the diagnosis of herpes simplex esophagitis. So far, in Japan, there have been, in the literatures, a total of 11 cases of herpes simplex esophagitis found in endoscopic examination, including our present case. Of these, four cases had malignant tumor as, underlying disease, one received an immunosuppressant after renal transplantation, two had hiatus hernia, and four had nasogastric intubation. However, there were three cases in which no clear underlying diseases were observed. Therefore, in performing endoscopy, it is important to pay a careful attention to possible presence of herpes simplex esophagitis.